Information and Communication Technologies : A World Bank Group Strategy - The World Bank Group (Washington, DC : World Bank, 2002)
This paper can be seen primarily as a business strategy for the World Bank Group's role in the development of information infrastructure, with some discussion of broader information and communication technologies issues facing the World Bank Group. It maps out a plan for expanding the institutional development capacity of the Global Information and Communication Technologies department and the regions in order to successfully implement the strategy, and discusses some issues connected with information technology quality assurance and improving the World Bank Group's capacity to ensure quality.
Includes bibliographical references.
ne 3/05/2018
Loans
Keywords: Information Technology; Communication